Notice of the Discovery of a Stone-Age Cist in a Large Cairn at Stroanfreggan, Parish of Dalry, Kirkcudbrightshire - Corrie, John (Proceedings of the Society of Antiquaries of Scotland, 1911)
The stone cist was damaged and partly emptied by workmen during road construction. It was within a large circular cairn. The cist lies almost exactly north and south. Its position is not in the centre of the cairn, but nearly midway between the centre and the line of circumference. It is constructed of four whinstone slabs inserted vertically into the subsoil. Artefacts include a flint knife, and traces of charcoal and comminuted bone. A few pieces of clay bear the distinct impression of finger prints.